Developmental Concepts: Qualitative Overview of Nigeria's Experience: Konsep Pembangunan: Tinjauan Kualitatif Pengalaman Nigeria - Majekodunmi, Samuel Ayodele; Olajide-Arise, Temi Omovigho (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2025)
The incidence of best brains and hands migrating from Nigeria to settle for a new life in the developed world has persistently increased. Similarly, organizations are relocating from Nigeria due to the rising cost of operations. Practically, all sectors in the Nigerian economy have continued to face shortages of skilful personnel. However, the health sector seemed to be the most affected. The concern about the current situation of low economic development leading to an exodus of energetic Nigerians seeking greener pastures elsewhere necessitates this study titled "Developmental Concepts: Qualitative Overview of Nigeria Experience". This is a qualitative study; the paper explores secondary sources to offer well-articulated conceptual clarification on different development concepts. The articulated concepts were logically analyzed. The findings from the analysis indicated that Nigeria has resources, both natural and human. In the past, the resources did not seem to be put to proper use. It is therefore concluded that the problem of Nigeria is not a lack of resources; instead, it is improper development of the resources and judicious usage of them to make life comfortable for all citizens. Therefore, this paper recommends that there should be judicious usage of available resources to benefit all Nigerians. Gejala migrasi tenaga ahli dan tenaga terampil Nigeria untuk menetap di negara maju terus meningkat. Demikian pula, banyak organisasi keluar dari Nigeria karena meningkatnya biaya operasi. Secara praktis, Nigeria terus menghadapi kekurangan tenaga terampil di semua sektor ekonomi. Sektor kesehatan merupakan sektor yang paling terpengaruh. Kekhawatiran tentang rendahnya pembangunan ekonomi saat ini mengarah pada eksodus warga Nigeria untuk mencari penghidupan yang lebih baik di tempat lain, melandasi pentingnya penelitian "Konsep Pembangunan: Tinjauan Kualitatif Pengalaman Nigeria". Penelitian ini merupakan penelitian kualitatif yang mengeksplorasi sumber-sumber sekunder mengklarifikasi konseptual tentang konsep-konsep pembangunan yang berbeda yang dianalisis secara logis. Penelitian menghasilkan temuan bahwa Nigeria memiliki sumber daya, baik sumber daya alam maupun sumber daya manusia. Di masa lalu, sumber daya tersebut belum dimanfaatkan dengan baik. Oleh karena itu, disimpulkan bahwa masalah Nigeria bukanlah kekurangan sumber daya, melainkan pengembangan sumber daya yang tidak tepat dan penggunaannya yang kurang bijaksana untuk membuat kehidupan lebih nyaman bagi semua warga negara. Oleh karena itu, seluruh sumber daya yang dimiliki Nigeria hendaknya dapat digunakan secara bijaksana untuk memberi manfaat bagi semua warga Nigeria.